Is there a Post-Marxist Criticism to the Decolonial Critique? (Journal of Decolonising Disciplines, 2021)
This article makes explicit a hidden tension between post-Marxism and decolonial studies, which points to a challenge for intercultural dialogue. While post-Marxism seeks to rehabilitate a universal foundation for the construction of truth claims—a universal already formed within Western modernity—the decolonial critique seeks to dismantle all universals connected to the myths of modernity and therefore demands a departure from the standpoint of the cultural periphery. In fact, Alain Badiou and Slavoj Žižek, like other post-Marxists, have been rather critical of the standpoints articulated by decolonialists who strive to include cultural differences and marginalised identities in the process of knowledge production, but the reality is that the decolonial critique, more so than post-Marxism, is well-supported by the historical evidence, thus demonstrating the need for Enrique Dussel calls a ‘transmodern pluriverse’ in the academic world. In pursuit of diffusing this tension between the post-Marxists and the decolonialists, this article calls for further investigation in terms of determining if real dialogue is possible between these two trajectories of thought.
Keywords: Post-Marxism, Transmodernity, Decolonisation, the Myth of Modernity